ANALYSIS OF DRUGS ASSORTMENT APPLIED FOR REHABILITATION TREATMENT IN NEUROLOGY DEPARTMENT OF HEALTH RESORT FOR PATIENTS INJURED IN EMERGENCY SITUATIONS - T. I. Kabakova; A. B. Zarbolganova (Фармация и фармакология (Пятигорск), 2015)
The article shows the results of assortment analysis of drugs applied in rehabilitation treatment of neurology patients in departmental health centers injured in terrorist attacks.